2016
DOI: 10.1021/acsbiomaterials.6b00162
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Antibacterial Borosilicate Glasses for Bone Tissue Engineering Applications

Abstract: Three novel borosilicate bioactive glasses (BBGs) were prepared and used to investigate their bioactive and antibacterial properties. The BBGs were prepared by melt-quenching using different glass modifiers, i.e. Mg 2+ , Ca 2+ , and Sr 2+ , and their amorphous nature was confirmed by X-ray diffraction. Scanning electron microscopy with energy dispersive X-ray spectroscopy allowed the visualization of apatite-like structures upon 7 days of immersion in simulated body fluid. BBG-Ca generated surface structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…We found that the presence of BBG-Sr glass particles improved the osteogenic differentiation of bone marrow mesenchymal stem cells (BM-MSCs) and induced the formation of mineralised tissue. We also demonstrated that BBG-Sr, at concentrations P18 mg/mL it was able to eradicate Pseudomonas aeruginosa bacterium [26]. Numerous reports have already associated Sr 2+ with bone therapeutic potential [19].…”
Section: Introductionsupporting
confidence: 53%
“…We found that the presence of BBG-Sr glass particles improved the osteogenic differentiation of bone marrow mesenchymal stem cells (BM-MSCs) and induced the formation of mineralised tissue. We also demonstrated that BBG-Sr, at concentrations P18 mg/mL it was able to eradicate Pseudomonas aeruginosa bacterium [26]. Numerous reports have already associated Sr 2+ with bone therapeutic potential [19].…”
Section: Introductionsupporting
confidence: 53%
“…The effect of BBGs' concentration on cell viability and proliferation was studied on a previous work (29,30).…”
Section: Potential Cytotoxic Effect Of Bbgs Leachables On Bm-mscsmentioning
confidence: 99%
“…The composition of BBGs was confirmed in a prior work by the use of X-ray fluorescence and follows the general formula 0.05Na 2 OxMgOyCaO(0.35-x-y)SrO0.20B 2 O 3 0.40SiO 2 (molar ratio, where x, y = 0.35 or 0.00, and x ≠ y). (30) Moreover, studies after immersion in SBF, showed that the studied BBGs are bioactive due to the formation of bone-like apatite structures onto their surface, and the constant release of ions to the reaction media over time (29).…”
mentioning
confidence: 99%
“…Bioglass nanoparticles were also used with bacterially derived poly(3-hydroxybutyrate) to fabricate bioactive composite film using a fermentation technique [ 275 ]. Different glass modifiers (Mg 2+ , Ca 2+ , and Sr 2+ ) were used to prepare borosilicate bioactive glasses through a melt-quenching technique which showed good antibacterial properties [ 276 ]. Poly(propylene fumarate) (PPF) was used to functionalize bioglass particles that enhance the bioactivity and cell adhesion, proliferation, and bone regeneration [ 277 ].…”
Section: Nanobiomaterialsmentioning
confidence: 99%